Ballistic Impact Response of Al0.1CoCrFeNi High‐Entropy Alloy. Issue 6 (22nd April 2020) - Muskeri, Saideep; Choudhuri, Deep; Jannotti, Philip A.; Schuster, Brian E.; Lloyd, Jeffrey T.; Mishra, Rajiv S.; Mukherjee, Sundeep
Abstract : High‐entropy alloys, consisting of multiple principal elements, represent a new paradigm in structural alloy design with excellent mechanical properties and potentially promising ballistic performance. Herein, the ballistic response of a single‐phase Al0.1 CoCrFeNi high‐entropy alloy is evaluated with spherical E52100 steel (RC60) projectiles at velocities ranging from 500 to 1000 m s −1 at normal obliquity, indicating failure by ductile–hole growth. A wide range of microstructural features are observed corresponding to varying degrees of deformation and the corresponding hardness maps are obtained. The microstructure in the partially penetrated condition is dominated by microbanding and microtwinning close to the crater wall. With striking velocity that result in plugging but not complete penetration, the deformation is dominated by twinning and crack initiation around adiabatic shear bands close to the exit hole. A high density of localized adiabatic shear bands and recrystallized grains are observed at impact velocities corresponding to full penetration. Highly deformed areas near the crater wall and narrow zones around shear bands show the maximum hardness, indicating significant work hardening of the material during penetration. Abstract : The ballistic response of a single‐phase Al0.1 CoCrFeNi high‐entropy alloy is evaluated with spherical E52100 steel (RC60) projectiles at velocities ranging from 500 to 1000 m s −1 at normal obliquity, indicating failure by ductile–hole growth. A wide range of microstructural features are observed, corresponding to varying degrees of deformation and the corresponding hardness maps are obtained.